2012
DOI: 10.1007/s00436-012-3127-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microglia activation between rats-derived cell and mice-derived cell after stimulating by soluble antigen of IV larva from Angiostrongylus cantonensis in vitro

Abstract: Angiostrongylus cantonensis is a rodent nematode. Adult worms of A. cantonensis live in the pulmonary arteries of rats. Humans and mice are accidental hosts or named nonpermissive hosts. The larva cannot develop into an adult worm and only causes serious eosinophilic meningitis or meningoencephalitis if humans or mice eat food containing larva of A. cantonensis in the third stage. The differing consequences largely depend on differing immune responses of the host to parasite during A. cantonensis invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…However, histamine did not induce the release of TNF-α in the N9 microglia cell line [37], possibly because the microglia cell line is less sensitive than primary cultured microglia. In addition, the N9 microglia cell line is mouse-derived, and there are differences in microglial activation between rat-derived and mouse-derived cells [38]. In the present study, we also found that histamine was able to induce enhanced ROS production.…”
Section: Discussionsupporting
confidence: 73%
“…However, histamine did not induce the release of TNF-α in the N9 microglia cell line [37], possibly because the microglia cell line is less sensitive than primary cultured microglia. In addition, the N9 microglia cell line is mouse-derived, and there are differences in microglial activation between rat-derived and mouse-derived cells [38]. In the present study, we also found that histamine was able to induce enhanced ROS production.…”
Section: Discussionsupporting
confidence: 73%
“…Contrary to LS, HSF triggered a significant production of NO in both astrocyte and microglia cultures. Similar effect (demonstrated at the level of enhanced iNOS expression) was shown for murine microglia treated in vitro with larval soluble antigen of the neurotropic nematode Angiostrongylus cantonensis [45]. As for T. regenti , NO production by glial cells might be associated with the in vivo occurring axonal damage [46, 47].…”
Section: Discussionmentioning
confidence: 60%
“…RANTES (25) and eotaxin (26) are two important proinflammatory chemokines that are produced by T cells and antigenpresenting cells such as macrophages and microglia. RANTES, a 68-amino acid-long polypeptide, is known to induce the migration and homing of classical lymphoid cells such as T cells and monocytes and other immune cells including basophils, eosinophils, natural killer cells, dendritic cells, and mast cells (27).…”
Section: Discussionmentioning
confidence: 99%